1988
DOI: 10.1021/ie00074a022
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium constant for the methyl tert-butyl ether vapor-phase synthesis

Abstract: The use of biased least-squares methods for the estimation of pulse-response coefficients in discrete-time process models is proposed. The two specific approaches considered here are partial least squares (PLS) and a method based on the singular value decomposition (SVD). Example applications

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 6 publications
2
17
0
Order By: Relevance
“…Catalyst activities expressed as conversions relative to equilibrium values (calculated according to data from Tejero et al [7]) are shown m Tables 1 and 2; in all the cases selectivity to MTBE formation was 100% An important deactivation was observed on SA-i catalysts while the other samples maintained activity along experiments of about four hours. It is to be noticed that in spite of having different acidities, the initial activity was the same for all SA-i samples.…”
Section: Resultsmentioning
confidence: 99%
“…Catalyst activities expressed as conversions relative to equilibrium values (calculated according to data from Tejero et al [7]) are shown m Tables 1 and 2; in all the cases selectivity to MTBE formation was 100% An important deactivation was observed on SA-i catalysts while the other samples maintained activity along experiments of about four hours. It is to be noticed that in spite of having different acidities, the initial activity was the same for all SA-i samples.…”
Section: Resultsmentioning
confidence: 99%
“…By using transformed compositions, these take the form of triangular charts. In Figures 3 and 4, the residue curve maps of the system are plotted in transformed compositions at 1 and 7 atm by employing UMR-UNIFAC and the equilibrium constant by Tejero et al 64 Table 3. CPE Results for Vapor-Phase MTBE Synthesis: Deviations from Molecular Simulation Data by Li ́sal et al 63 (5 Data Points) K eq source Tejero et al 64 Li ́sal et al 63…”
Section: Eos With the Uniquac Or Unifac Activity Coefficient Model Vi...mentioning
confidence: 99%
“…In this work, both cases of vapor and liquid phase reaction are studied, with three different equilibrium constants in each case: two from the literature and the other one calculated from the van't Hoff equation with temperature dependent reaction enthalpy. For the vapor phase reaction, the Gibbs energies of formation of the components are obtained from Tejero et al [160], and enthalpies of formation and heat capacities are retrieved from Lísal et al [159]. For the liquid phase reaction, all properties are taken from Badia et al [146].…”
Section: Mtbe Synthesismentioning
confidence: 99%
“…By using transformed compositions, these take the form of triangular charts. In Figure 11.3 and Figure 11.4 the residue curve maps of the system are plotted in transformed compositions at 1 and 7 atm by employing UMR-UNIFAC and the equilibrium constant by Tejero et al [160].…”
Section: Mtbe Synthesismentioning
confidence: 99%
See 1 more Smart Citation